1997
DOI: 10.1161/01.cir.96.9.2944
|View full text |Cite
|
Sign up to set email alerts
|

ECG-Gated Three-dimensional Intravascular Ultrasound

Abstract: ECG-gated acquisition of 3D IVUS image sets is feasible and permits the application of automated contour detection to provide reproducible measurements of the lumen and atherosclerotic plaque CSA and volume in a relatively short analysis time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
45
0

Year Published

1998
1998
2007
2007

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 172 publications
(48 citation statements)
references
References 47 publications
3
45
0
Order By: Relevance
“…12 Intraobserver and interobserver variabilities of this system have also been determined in clinical protocols. 9 Intraobserver variability assessed with analysis of the IVUS volumetric studies at intervals of Ն3 months has been reported: Ϫ0.4Ϯ1.1% in lumen volume, Ϫ0.4Ϯ0.6% in total vessel volume, and Ϫ0.3Ϯ1.0% in plaque volume with ECG-gated motorized pullback.…”
Section: Ivus Image Acquisition Analysis Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…12 Intraobserver and interobserver variabilities of this system have also been determined in clinical protocols. 9 Intraobserver variability assessed with analysis of the IVUS volumetric studies at intervals of Ն3 months has been reported: Ϫ0.4Ϯ1.1% in lumen volume, Ϫ0.4Ϯ0.6% in total vessel volume, and Ϫ0.3Ϯ1.0% in plaque volume with ECG-gated motorized pullback.…”
Section: Ivus Image Acquisition Analysis Systemmentioning
confidence: 99%
“…5,9 In brief, the segment subject to 3-D reconstruction was examined with a 30-MHz singleelement mechanical transducer IVUS system (ClearView, CVIS; Boston Scientific Corp). ECG-gated 3-D IVUS image acquisition and digitization were performed with a computerized workstation (EchoScan; TomTec).…”
Section: Ivus Image Acquisition Analysis Systemmentioning
confidence: 99%
“…Furthermore, individual patients were imaged with the same system at index and follow-up. 3D (ECG-gated) IVUS analysis 34 may be superior for the assessment of coronary dimensions and provides volumetric data. In addition, sophisticated computer-aided gray-scale IVUS analyses 15 or radiofrequency IVUS analyses 35 may be superior to visual IVUS analysis of plaque composition.…”
Section: Limitationsmentioning
confidence: 99%
“…As a tomographic imaging technique, intravascular ultrasound (IVUS) allows the visualization of atherosclerotic plaques in vivo. [2][3][4][5][6] In standard IVUS gray-scale images, calcified regions of plaque and dense fibrous components generally reflect ultrasound energy well and thus appear bright and homogeneous on IVUS images. Conversely, regions of low echo reflectance in IVUS images are usually labeled as "soft" or "mixed" plaque.…”
mentioning
confidence: 99%